PRIVATISASI BUMN DAN PENEGAKAN GOOD CORPORATE GOVERNANCE DAN KINERJA BUMN - Ilya Avianti (KINERJA, 2006)
Privatization of State Owned Companies (BUMN) represents government efforts in orderto improve performance of such companies through ownership and transfer of control to other parties (private sectors). However, this privatization, in fact, has not yet been able to increase profitability and maintain good corporate governance. The efforts to create effectiveness and efficiency of such companies could be done by enhancing public ownership, enforcing corporate governance principles, and empowering role of audit committee and independent director/commissioner.Keywords: Privatization, State Owned Companies, Corporate Governance Enforcement andPerformance